Comorbilidad como factor pronóstico de mortalidad en ancianos hospitalizados por neumonía adquirida en la comunidad - Mesía Vidal, Eric Aldo (2014)
To demonstrate that comorbidity is a mortality prognostic factor in elderly patients with community-acquired pneumonia. PATIENTS AND METHODS: It was a retrospective cohort study. We’d included the medical records of elderly patients hospitalized for communityacquired pneumonia in Internal and Respiratory Medicine services from Belen Hospital during the period January 2007 to December 2012. The sample was 98 patients for each cohort. One cohort was constituted by patients with Charlson Comorbidity Index ≥ 2 and the other one with Charlson Comorbidity Index < 2. The endpoint was in-hospital mortality. We applied chi-square; determine relative risk and the 95% - confidence intervals. RESULTS: General mortality was 17.85%. It was significative greatest in the exposed cohort (25.5% vs. 10.2%; p < 0.05). Hospital length of stay was significative greatest in the exposed cohort (p < 0.05). The prevailing comorbidities among deceased patients were chronic respiratory disease and heart failure CONCLUSION: Comorbidity is associated with mortality in elderly patients hospitalized for community-acquired pneumonia